Finite element analysis of heat treated wood filled styrene maleic anhydride (SMA) copolymer composites : Analiza kompozita od kopolimera stirena i anhidrida maleinske kiseline (SMA) punjenih pregrijanim drvom metodom konačnih elemenata - Zor, Mustafa (Array, 2019)
The computer aided three dimensional static analyses of the specimens was done by using the Finite Element Method (FEM) and obtained data was compared with actual test data. The aim of this study is to compare the deformation/stress analyses with FEM analysis results of styrene maleic anhydride (SMA) copolymer composites. The heat treated wood/SMA copolymer composites were produced from different loadings (from 10 to 30 wt. %) of heat treated and untreated eastern white pine wood flours (Pinus strobus L.). All formulations of wood flour/SMA copolymer composites were produced by melt compounding through injection molding. The deformation/stress results obtained from the experimental solutions are very close to the results obtained from the numerical solutions (SAP2000 V17). As a result, it can be said that it is beneficial to use the FEM in the engineering design approach after the data obtained by the experimental solutions as meaningful values after application of the FEM.